Preparation method of self-adhesive high-strength chitosan oligosaccharide composite hydrogel with anti-freezing property
Patent Information
- Application Number
- CN202311455543.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-02
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-11-02
AI Technical Summary
Traditional hydrogels lose their toughness and conductivity when frozen at low temperatures, resulting in poor mechanical properties. Furthermore, the expensive preparation methods for dopamine limit their widespread application.
A PAA/TA/CSO composite hydrogel was prepared by using polyacrylic acid (PAA) as the crosslinking network, with tannic acid (TA) and chitosan oligosaccharide (CSO) forming physical crosslinking points through hydrogen bonding, and adding lithium chloride (LiCl) to improve its antifreeze ability and adhesion properties.
The prepared hydrogel retains conductivity at -20℃, has a tensile strength of 0.05MPa-0.176MPa, a fracture strain of 600%-1666%, and an adhesion strength of up to 16KPa. It is inexpensive and suitable for a variety of substrates.
Smart Images

Figure CN117402302B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional materials, and specifically to a method for preparing a self-adhesive high-strength chitosan oligosaccharide composite hydrogel with antifreeze properties. Background Technology
[0002] Hydrogels are soft materials composed of a three-dimensional cross-linked network structure and water. They possess excellent properties such as strong water retention, good biocompatibility, and controllable mechanical properties, and are widely used in wound dressings, tissue engineering, and wearable sensing. However, traditional hydrogels suffer from poor mechanical properties and low viscosity. Furthermore, due to their high water content, hydrogels freeze below 0°C, causing them to lose toughness and conductivity, limiting their application at low temperatures. In recent years, designing a self-adhesive, high-strength hydrogel with antifreeze properties has become a significant potential solution for applications in various complex environments.
[0003] Introducing inorganic salt ions into hydrogels is one of the most common methods to improve their freeze-thaw resistance. This not only lowers the freezing point and inhibits ice crystal formation but also enhances their electrical conductivity. However, excessive salt in the hydrogel weakens the intermolecular hydrogen bonds between the components, leading to a decrease in mechanical properties, which is detrimental to the practical applications of hydrogels. Currently, the mechanical properties of hydrogels can be improved through the design of strong hydrogen bonds, resulting in a denser hydrogel network and closer bonding between the components, thereby enhancing the hydrogel's fracture strain and tensile strength.
[0004] Introducing adhesive functional components and designing hydrogel structures are effective methods to improve the adhesiveness of hydrogels. In recent years, hydrogels based on dopamine, containing catechol groups, have been widely reported to significantly enhance adhesiveness. However, due to the high cost of dopamine, its application has not been widespread. Therefore, it is essential to utilize abundant natural raw materials such as tannic acid and chitosan oligosaccharides to prepare self-adhesive high-strength composite hydrogels with antifreeze properties. Summary of the Invention
[0005] This invention aims to overcome the shortcomings of existing hydrogels, such as poor mechanical properties and insufficient functionality, and provides a method for preparing a high-strength chitosan oligosaccharide composite hydrogel with widely available raw materials and antifreeze and self-adhesive properties. The hydrogel is a PAA / TA / CSO / LiCl composite hydrogel, with polyacrylic acid (PAA) as the crosslinking network. Tannic acid (TA) and chitosan oligosaccharide (CSO) interact with the PAA molecular chains through hydrogen bonding, which improves the mechanical and adhesive properties of the gel. The introduction of lithium chloride (LiCl) endows the composite hydrogel with a certain antifreeze ability.
[0006] The technical solution of the present invention is as follows:
[0007] A method for preparing a self-adhesive high-strength chitosan oligosaccharide composite hydrogel with antifreeze properties, characterized by being prepared according to the following steps in sequence:
[0008] (1) Prepare a lithium chloride solution;
[0009] (2) Add acrylic acid to the solution obtained in step (1) and stir evenly at room temperature to obtain A;
[0010] (3) Add tannic acid and chitosan oligosaccharide to A in sequence and stir at room temperature for 30 minutes to obtain B;
[0011] (4) Add crosslinking agent to B and stir for 1 hour. After full crosslinking, add initiator and stir for 30 minutes to initiate polymerization to obtain C;
[0012] (5) Transfer C to a mold and then put it in an oven to heat. After heating, place it at room temperature for 3 hours to obtain a self-adhesive high-strength chitosan oligosaccharide composite hydrogel with antifreeze properties.
[0013] As a first limitation of the present invention, in step (1), the concentration of the lithium chloride solution is 0.5-2M.
[0014] As a second limitation of the present invention, in step (2), the acrylic acid solid content is 20%-50%.
[0015] As a third limitation of the present invention, in step (3), the tannic acid content is 10-30 mg / mL.
[0016] As a fourth limitation of the present invention, in step (3), the content of chitosan oligosaccharide is 10-50 mg / mL.
[0017] The present invention has a reasonable ratio of acrylic acid, tannic acid, chitosan oligosaccharide and lithium chloride. The content ratio of each component affects the content of hydrogen bonds between molecules of the polymerized hydrogel, the adhesion performance and mechanical strength. Specifically, the polymerization reaction of the present application occurs at high temperature. The strong hydrogen bond structure formed by tannic acid and chitosan oligosaccharide with polyacrylic acid improves the mechanical properties of the hydrogel, making the hydrogel network denser and the components connected by hydrogen bonds more tightly. This enhances the fracture strain and fracture strength of the hydrogel. Therefore, only within the ratio range of the present invention can a self-adhesive high-strength composite hydrogel with antifreeze properties be formed.
[0018] As a fifth limitation of the present invention, in step (4), the crosslinking agent is N,N'-methylenebisacrylamide, and the molar amount of which is added accounts for 0.01-0.1% of the total molar amount of the monomer.
[0019] As a sixth limitation of the present invention, in step (4), the initiator is ammonium persulfate, and the molar amount of which is added accounts for 0.5-1% of the total molar amount of the monomer.
[0020] The present invention also has a limitation: in step (5), the temperature of the oven is 50-80℃ and the heating time is 1.5-6h.
[0021] The preparation method described above in this invention is a whole in which each step is closely related and inseparable.
[0022] In the reaction system of this invention, polyacrylic acid serves as the polymer backbone, where the carboxyl groups can electrostatically interact with various surfaces, adhering to a variety of substrates. After tannic acid and chitosan oligosaccharides are introduced into the polymer network, the abundant catechol groups in the tannic acid and the hydroxyl groups in the chitosan oligosaccharides, on the one hand, enhance the interfacial adhesion strength of the hydrogel through physical interactions, particularly hydrogen bonding; on the other hand, they improve the mechanical properties of the gel through interactions between hydrogen bonds and the polyacrylic acid molecular chains. Lithium chloride dissociates in aqueous solution... + and Cl - By binding 4 or 6 water molecules respectively, the interactions between water molecules are disrupted, preventing them from freezing and giving the hydrogel a certain degree of antifreeze ability. In addition, the addition of lithium chloride reduces the free water content and increases the bound water content of the hydrogel. The connection between the components becomes tighter due to the increased bound water content, thereby further improving the mechanical properties of the hydrogel.
[0023] The beneficial effects achieved by the present invention after adopting the above technical solution are as follows:
[0024] 1. This invention uses thermal polymerization to prepare hydrogels, which is simple, highly controllable, and has a short preparation cycle.
[0025] 2. This invention uses acrylic acid, tannic acid and chitosan oligosaccharide as raw materials, which are abundant, inexpensive and biocompatible.
[0026] 3. The hydrogel prepared by this invention has good antifreeze properties and superior mechanical properties. The hydrogel product can still maintain conductivity at -20℃, with tensile strength of 0.05MPa-0.176MPa and fracture strain of 600%-1666%.
[0027] 4. The hydrogel prepared by this invention has good adhesion properties and a wide range of applications. It can adhere to a variety of substrates, such as the surfaces of glass bottles, copper sheets, clips, PMMA, etc., with an adhesion strength of up to 16 kPa.
[0028] This invention is applicable to the preparation of self-adhesive high-strength chitosan oligosaccharide composite hydrogels with antifreeze properties.
[0029] The specific embodiments of the present invention will now be described in further detail with reference to the accompanying drawings. Attached Figure Description
[0030] Figure 1 The differential scanning calorimetry characterization diagrams are for the hydrogel and its control group.
[0031] Figure 2 Figure 1 shows the tensile properties of the hydrogels, where: Figure 2a shows the tensile mechanical properties of hydrogels with different amounts of tannic acid, and Figure 3b shows the tensile mechanical properties of hydrogels with different amounts of chitosan oligosaccharide.
[0032] Figure 3 Figure 1 shows the adhesion properties of the hydrogel, where: Figure 2a shows the adhesion effect of the hydrogel on substrates such as glass bottles, copper sheets, clips, PMMA, glass slides, rubber stoppers, insulating tape and weights; Figure 3b shows the adhesion strength of the hydrogel on different substrates. Detailed Implementation
[0033] Unless otherwise specified, all reagents used in the following embodiments are commercially available reagents, and all experimental and detection methods used in the following embodiments are existing experimental and detection methods.
[0034] Examples 1-5 below respectively prepare a self-adhesive high-strength chitosan oligosaccharide composite hydrogel with antifreeze properties. The reagents used mainly include the following: lithium chloride, acrylic acid, tannic acid, chitosan oligosaccharide, N,N'-methylenebisacrylamide, ammonium persulfate, and deionized water.
[0035] Example 1
[0036] This embodiment prepares a self-adhesive high-strength chitosan oligosaccharide composite hydrogel with antifreeze properties, and the following steps are performed in sequence:
[0037] (1) Prepare a 1M lithium chloride solution;
[0038] (2) Add acrylic acid with a solid content of 30% to the solution obtained in step (1) and stir evenly at room temperature;
[0039] (3) After the acrylic acid is stirred evenly, add 10 mg / mL tannic acid and 40 mg / mL chitosan oligosaccharide in sequence, and stir at room temperature for 30 min;
[0040] (4) Add crosslinking agent N,N'-methylenebisacrylamide to the solution formed in step (3), the molar amount of which accounts for 0.01% of the total molar amount of the monomer, stir for 1 hour, and after full crosslinking, add initiator ammonium persulfate, the molar amount of which accounts for 0.5% of the total molar amount of the monomer, and stir for 30 minutes to initiate polymerization;
[0041] (5) Transfer the solution obtained in step (4) into a mold, and then place it in an oven at 60°C for 4 hours. After heating, place it at room temperature for 3 hours to obtain a self-adhesive high-strength chitosan oligosaccharide composite hydrogel with antifreeze properties.
[0042] Example 2
[0043] This embodiment prepares a self-adhesive high-strength chitosan oligosaccharide composite hydrogel with antifreeze properties, and the following steps are performed in sequence:
[0044] (1) Prepare a 0.5M lithium chloride solution;
[0045] (2) Add acrylic acid with a solid content of 20% to the solution obtained in step (1) and stir evenly at room temperature;
[0046] (3) After the acrylic acid is stirred evenly, add 10 mg / mL tannic acid and 10 mg / mL chitosan oligosaccharide in sequence and stir at room temperature for 30 min;
[0047] (4) Add crosslinking agent N,N'-methylenebisacrylamide to the solution formed in step (3), the molar amount of which accounts for 0.03% of the total molar amount of monomers, stir for 1 hour, and after full crosslinking, add initiator ammonium persulfate, the molar amount of which accounts for 1% of the total molar amount of monomers, and stir for 30 minutes to initiate polymerization.
[0048] (5) Transfer the solution obtained in step (4) into a mold, and then place it in an oven at 50°C for 6 hours. After heating, place it at room temperature for 3 hours to obtain a self-adhesive high-strength chitosan oligosaccharide composite hydrogel with antifreeze properties.
[0049] Example 3
[0050] This embodiment prepares a self-adhesive high-strength chitosan oligosaccharide composite hydrogel with antifreeze properties, and the following steps are performed in sequence:
[0051] (1) Prepare a 0.5M lithium chloride solution;
[0052] (2) Add acrylic acid with a solid content of 30% to the solution obtained in step (1) and stir evenly at room temperature;
[0053] (3) After the acrylic acid is stirred evenly, add 20 mg / mL tannic acid and 20 mg / mL chitosan oligosaccharide in sequence and stir at room temperature for 30 min;
[0054] (4) Add crosslinking agent N,N'-methylenebisacrylamide to the solution formed in step (3), the molar amount of which accounts for 0.05% of the total molar amount of monomers, stir for 1 hour, and after full crosslinking, add initiator ammonium persulfate, the molar amount of which accounts for 0.8% of the total molar amount of monomers, and stir for 30 minutes to initiate polymerization;
[0055] (5) Transfer the solution obtained in step (4) into a mold, and then place it in an oven at 60°C for 6 hours. After heating, place it at room temperature for 3 hours to obtain a self-adhesive high-strength chitosan oligosaccharide composite hydrogel with antifreeze properties.
[0056] Example 4
[0057] This embodiment prepares a self-adhesive high-strength chitosan oligosaccharide composite hydrogel with antifreeze properties, and the following steps are performed in sequence:
[0058] (1) Prepare a 1.5M lithium chloride solution;
[0059] (2) Add acrylic acid with a solid content of 40% to the solution obtained in step (1) and stir evenly at room temperature;
[0060] (3) After the acrylic acid is stirred evenly, add 30 mg / mL tannic acid and 30 mg / mL chitosan oligosaccharide in sequence and stir at room temperature for 30 min;
[0061] (4) Add crosslinking agent N,N'-methylenebisacrylamide to the solution formed in step (3), the molar amount of which accounts for 0.07% of the total molar amount of monomers, stir for 1 hour, and after full crosslinking, add initiator ammonium persulfate, the molar amount of which accounts for 0.6% of the total molar amount of monomers, and stir for 30 minutes to initiate polymerization;
[0062] (5) Transfer the solution obtained in step (4) into a mold, and then place it in an oven at 70°C for 3 hours. After heating, place it at room temperature for 3 hours to obtain a self-adhesive high-strength chitosan oligosaccharide composite hydrogel with antifreeze properties.
[0063] Example 5
[0064] This embodiment prepares a self-adhesive high-strength chitosan oligosaccharide composite hydrogel with antifreeze properties, and the following steps are performed in sequence:
[0065] (1) Prepare a 2M lithium chloride solution;
[0066] (2) Add acrylic acid with a solid content of 50% to the solution obtained in step (1) and stir evenly at room temperature;
[0067] (3) After the acrylic acid is stirred evenly, add 30 mg / mL tannic acid and 50 mg / mL chitosan oligosaccharide in sequence and stir at room temperature for 30 min;
[0068] (4) Add crosslinking agent N,N'-methylenebisacrylamide to the solution formed in step (3), the molar amount of which accounts for 0.1% of the total molar amount of monomers, stir for 1 hour, and after full crosslinking, add initiator ammonium persulfate, the molar amount of which accounts for 0.5% of the total molar amount of monomers, and stir for 30 minutes to initiate polymerization;
[0069] (5) Transfer the solution obtained in step (4) into a mold, and then place it in an oven at 80°C for 1.5 hours. After heating, place it at room temperature for 3 hours to obtain a self-adhesive high-strength chitosan oligosaccharide composite hydrogel with antifreeze properties.
[0070] Example 6 Performance Test
[0071] A series of performance tests were performed on the material prepared in Example 1. See the attached table for specific results. Figures 1-3 As shown.
[0072] Figure 1 The antifreeze properties of the hydrogel were investigated using differential scanning calorimetry (DSC). As shown in the figure, after the addition of lithium chloride, the Li₂ dissociates in the aqueous solution... + and Cl - It can bind 4 or 6 water molecules and disrupt the interaction between water molecules, so introducing lithium chloride into hydrogels can prevent them from freezing.
[0073] Figure 2 The graphs show the mechanical properties of the hydrogel and its control group (products prepared with different amounts of tannic acid and chitosan oligosaccharide, similar to the preparation process in Example 1) at room temperature. Graph a shows the effect of different tannic acid contents on mechanical properties, and graph b shows the effect of different chitosan oligosaccharide contents on mechanical properties. The graphs show that the strain of the gel increases with increasing tannic acid content; both the stress and strain of the hydrogel increase with increasing chitosan oligosaccharide content. When the chitosan oligosaccharide content is 40 mg / mL, the hydrogel strain reaches a maximum of 1355%, and the tensile strength is 0.162 MPa. Further increases in chitosan oligosaccharide content lead to a decrease in both strength and strain. This is because increased chitosan oligosaccharide content makes the hydrogel network denser, and the components connected by hydrogen bonds become more tightly linked, thus enhancing the hydrogel's fracture strain and fracture strength. However, excessive chitosan oligosaccharide leads to the formation of too many polyacrylic acid crystalline regions, causing the hydrogel to become rigid and reducing its tensile properties.
[0074] Figure 3The graph shows the adhesion properties of the hydrogel, which adheres to various substrates including glass bottles, copper sheets, clips, PMMA, glass slides, rubber stoppers, insulating tape, and weights. Overlap shear tests were used to further quantify the adhesion strength of the hydrogel to different materials, such as PMMA, PVC, glass sheets, stainless steel sheets, silicone, filter paper, and images. The results are shown below. Figure 3 As shown in b, the adhesion strength can reach up to 16 kPa.
[0075] Comparative Example 1
[0076] In this embodiment, differential scanning calorimetry was performed on the prepared product to compare the effect of lithium chloride introduction on the low-temperature resistance of the hydrogel. The following experiments were conducted:
[0077] Group A: The hydrogel prepared in this group was similar to that in Example 1, except that lithium chloride was not introduced in step (1), and deionized water was used as the solvent. The prepared hydrogel product underwent performance testing (DSC testing), and the results are as follows: Figure 1 It can be seen that the hydrogel without lithium chloride has a sharp exothermic peak at -17.1℃ and an endothermic peak at -0℃, indicating that the free water in the polyacrylic acid crosslinked network will freeze into ice crystals at -17.1℃.
[0078] Group B: The hydrogel prepared in Example 1 was tested. The hydrogel with added lithium chloride had an exothermic peak at -30.1℃ and an endothermic peak at -15℃. Both peaks shifted towards lower temperatures and became wider and smaller, indicating that the hydrogel containing lithium chloride has antifreeze properties.
[0079] Comparative Example 2
[0080] This embodiment compares the effect of tannic acid content on the mechanical properties of hydrogels, and the following experiments were conducted.
[0081] Group A: The hydrogel prepared in this group lacked the introduction of tannic acid compared to the preparation process in Example 1.
[0082] Group B: The hydrogel prepared in this group was obtained according to the procedure in Example 1.
[0083] The properties of the hydrogels prepared in the above groups were tested, and it was found that the strain of the hydrogel in group A without the introduction of tannic acid was 510% and the tensile strength was 0.114 MPa, which was significantly worse than that of the hydrogel prepared in this application.
[0084] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a self-adhesive high-strength chitosan oligosaccharide composite hydrogel with antifreeze properties, characterized in that, It is prepared according to the following steps: (1) Prepare a lithium chloride solution with a concentration of 0.5-2 M; (2) Add acrylic acid to the solution obtained in step (1) and stir until homogeneous at room temperature to obtain A; (3) Add tannic acid and chitosan oligosaccharide to A in sequence and stir at room temperature for 30 min to obtain B; (4) Add crosslinking agent to B and stir for 1 h. After full crosslinking, add initiator and stir for 30 min to initiate polymerization to obtain C; (5) Transfer C to a mold and then place it in an oven to heat. After heating, place it at room temperature for 3 hours to obtain a self-adhesive high-strength chitosan oligosaccharide composite hydrogel with antifreeze properties.
2. The method for preparing a self-adhesive high-strength chitosan oligosaccharide composite hydrogel with antifreeze properties according to claim 1, characterized in that, In step (2), the acrylic acid solid content is 20%-50%.
3. The method for preparing a self-adhesive high-strength chitosan oligosaccharide composite hydrogel with antifreeze properties according to claim 1, characterized in that, In step (3), the tannic acid content is 10-30 mg / mL.
4. The method for preparing a self-adhesive high-strength chitosan oligosaccharide composite hydrogel with antifreeze properties according to claim 1, characterized in that, In step (3), the content of chitosan oligosaccharide is 10-50 mg / mL.
5. The method for preparing a self-adhesive high-strength chitosan oligosaccharide composite hydrogel with antifreeze properties according to claim 1, characterized in that, In step (4), the crosslinking agent is N,N'-methylenebisacrylamide, and the molar amount of it added accounts for 0.01-0.1% of the total molar amount of the monomer.
6. The method for preparing a self-adhesive high-strength chitosan oligosaccharide composite hydrogel with antifreeze properties according to claim 1, characterized in that, In step (4), the initiator is ammonium persulfate, and the molar amount of it added accounts for 0.5-1% of the total molar amount of the monomer.
7. A method for preparing a self-adhesive high-strength chitosan oligosaccharide composite hydrogel with antifreeze properties according to any one of claims 1-6, characterized in that, In step (5), the temperature of the oven is 50-80℃ and the heating time is 1.5-6h.
Citation Information
Patent Citations
Silk fibroin-based adhesive anti-freezing conductive hydrogel and preparation method thereof
CN114133594A
